The Influence and Contribution of KH. Imam Zarkasyi in Islamic Educational Thought - Burhan Ibnu Hazin; Maragustam Siregar (International Forum of Researchers and Lecturers, 2025)
This paper explores the educational philosophy of KH. Imam Zarkasyi, the founder of Pondok Modern Darussalam Gontor, and his significant contributions to modernizing Islamic education in Indonesia. Imam Zarkasyi's approach redefined the traditional pesantren model by integrating religious and secular education to prepare students for the challenges of the modern world. His educational philosophy emphasized a balance between moral, intellectual, and spiritual development, with the goal of producing independent, ethical, and globally aware graduates. This study examines the background and biography of Imam Zarkasyi, the core educational values he implemented at Gontor, and his lasting impact on contemporary Islamic education in Indonesia. Through a qualitative literature review of primary and secondary sources, this research identifies Gontor’s education system as a model of Islamic education that fosters both character and knowledge, contributing to the broader reform of pesantren education in Indonesia.